Hormonal changes of intimate partner violence perpetrators in response to brief social contact with women. Issue 1 (4th October 2021) - van der Meij, Leander; Pulopulos, Matias M.; Hidalgo, Vanesa; Almela, Mercedes; Lila, Marisol; Roney, James R.; Salvador, Alicia
Abstract: This study investigated whether men with a history of real‐life aggressive, dominant behavior show increases in testosterone and cortisol levels after brief social contact with women. Furthermore, we tested the prediction that such changes in hormones would be larger than those observed previously in young male students. Sixty‐seven male participants convicted of intimate partner violence (IPV) either had brief social contact with a female confederate (experimental condition) or a male confederate (control condition). We also performed meta‐analyses to investigate whether IPV perpetrators' hormonal responses were larger than the typical responses of young male students in prior studies. All statistical analyses were preregistered. Change in testosterone did not differ across experimental conditions, and testosterone in the IPV perpetrators actually declined from baseline in the female confederate condition. Our meta‐analysis showed that this testosterone decrease was different from the testosterone increase typically observed in young male students. The cortisol levels of IPV perpetrators did not change in response to contact with women. This result was consistent with our meta‐analysis since young male students also did not experience a cortisol change in response to interactions with women. In sum, our findings provide no evidence that male IPV perpetrators exhibit larger hormone increases to brief interactions with women, although it is possible that the men in this sample did not perceive the social contact period as a courtship opportunity. These results suggest that hormone reactivity to social encounters may differ across subject populations and depend on how subjects perceive social situations within laboratory settings.